A Novel Polyaniline Nanowire Arrays/Three‐Dimensional Graphene Composite for Supercapacitor. Issue 35 (17th September 2020) - Gao, Xin; Zhang, Hengwei; Yue, Hongyan; Yao, Fei; Zhang, Xiaohua; Guo, Erjun; Ma, Yingyi; Wang, Zengze; Wang, Yuanbo
Abstract: It is an effective way to obtain high performance supercapacitors by increasing the surface area and conductivity of electrode materials. In this paper, three‐dimensional (3D) graphene with a small pore size, good electrical conductivity and high mechanical strength is fabricated by chemical vapor deposition using nickel nanoparticles as the template. Then, a polyaniline nanowire arrays (PANI NWAs)/3D graphene composite is fabricated by in‐situ polymerization. Due to the high conductivity and unique nano‐structure, the as‐prepared PANI NWAs/3D graphene composite exhibits an excellent capacitance of 680 F g −1 at current density of 1 A g −1 . Moreover, a symmetric supercapacitor based on the PANI NWAs/3D graphene composite is assembled, and it shows an energy density of 6.43 Wh kg −1 at a power density of 0.4 kW kg −1 . The assembled supercapacitor also exhibits a good cycling stability, which retains 78 % of its initial specific capacitance after 1000 cycles. Abstract : Three‐dimentional (3D) graphene was prepared by chemical vapor deposition using nickel nanoparticles as the template and polyaniline nanowire arrays (PANI NWAs) were grown on the surface of 3D graphene by in‐situ polymerization. 3D graphene provides electrically conductive channels for the PANI NWAs anchored on it and PANI NWAs with small diameters can enhance electrode specific surface areas and provide a high pseudocapacitance.